Evidence for macromolecular protein rings in the absence of bulk water. - Ruotolo, B; Giles, K; Campuzano, I; Sandercock, A; Bateman, R; Robinson, C (2005)
We have examined the architecture of a protein complex in the absence of bulk water. By determining collision cross sections of assemblies of the trp RNA binding protein, TRAP, we established that the 11-membered ring topology of the complex can be maintained within a mass spectrometer. We also found that the binding of tryptophan enhances the stability of the ring structure and that addition of a specific RNA molecule increases the size of the complex and prevents structural collapse. These results provide definitive evidence that protein quaternary structure can be maintained in the absence of bulk water and highlight the potential of ion mobility separation for defining shapes of heterogeneous macromolecular assemblies.